Anmeldelse af Democracy and Prosperity: Reinventing Capitalism Through a Turbulent Century - Andersen, Magnus; Etzerodt, Søren Frank (Politica, 2019)
Democracy and Prosperity: Reinventing Capitalism Through a Turbulent Century, Torben Iversen and David Soskice. Princeton University Press, 2019 (anmeldt af Magnus Andersen og Søren Frank Etzerodt)